Molecular attribute-driven hybrid SEI engineering for durable silicon anodes - Yijie Lin; Yingkang Deng; Yuling Fu; Mingjun Ma; Haolei Chen; Xinqi Chen; Shuhan Chen; Jiarong He; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2026)

Identification of functional hotspots via hybrid nuclear magnetic Resonance-Computational strategy for directed evolution of large enzymes - Yihao Chen; Zhou Gong; Xiaoling Zhao; Ali Raza; Mingjun Zhu; Zhiqing Tao; Wenhui Li; Xu Zhang; Maili Liu; Lichun He (Bioresource Technology, 2026)

Impacts of long-term fertilizer reduction and organic substitution on microbe-mediated multi-nutrient in agricultural ecosystems - Zhenling Li; Jiawei Ying; Xiaokang He; Yangyang Li; Guangchun Shan; Chenghong Feng; Mingjun Ding; Gaoxiang Huang; Jia Liu (Agriculture, Ecosystems & Environment, 2026)

Dynamic profiling of myogenesis in developing ovine skeletal muscle - Weiwei Duan; Zhenzhen Gu; Chenxi Liu; Wenrong Li; Sangang He; Bin Han; Lu Shi; Mingjun Liu (Meat Science, 2026)

Effects of combined humic-microbial amendment on the growth of pakchoi and soil improvement for coal mine subsided area - Huan He; Wenqing Mao; Xitong Heng; Juan Cheng; Mingjun Cao; Qinghe Cao; Zhilin Zhou; Xiuxiang Tao; Gordana Medunić; Zaixing Huang (Environmental Research, 2026)

A high-accuracy stacking model for automatic identification of aeolian saltating tracks in high-speed pictures - Mengjie Pu; Fanmin Mei; Chuan Lin; Mingjun Sui; Hongda Chen; Shenyang He; Weikai Wang; Chang Zhou; Jin Su; Jinguang Chen (Aeolian Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Organic substitution for synthetic fertilizer mitigates the negative effects of warming on soil quality, greenhouse gas emissions, and soybean yields - Xiaoyu Wang; Jiangsen Chu; Mengyou Zhang; Mingjun Hou; Ke Zheng; Leili Lin; Zhengjun Yan; Xiaoxiao Li; Zhao Che; He Song; Gong Wu (Field Crops Research, 2026)

Sustainable soil management in acidic paddy fields: liming and biochar application reduce greenhouse gas emissions while enhancing rice yields - Gong Wu; Xiaoyu Wang; Xing Wei; Mengyou Zhang; Jiangseng Chu; Mingjun Hou; Leili Lin; Yang Chen; Zhao Che; Xiaoxiao Li; Can Zhang; He Song (Journal of Environmental Management, 2026)

Agricultural plastic films reshape soil microplastic distribution, nitrogen cycle and ecological risks in facility agriculture - Hao Wang; Gaoxiang Huang; Xiaokang He; Guangchun Shan; Zhenling Li; Mingjun Ding; Chenghong Feng; Caixia Yan (Journal of Hazardous Materials, 2025)

Human traffic intensity alters the soil microbial community composition, diversity, and structure in subtropical urban green spaces - Abdul Baess Keyhani; Wei He; Mingjun Teng; Zhaogui Yan; Monira Fayaz; Zhaohui Peng; Yangyang Zhang; Safir Ahmad Tamim; Xiuyuan Wang; Zemin Han; Pengcheng Wang (Applied Soil Ecology, 2025)

Rapid visual field detection of Pratylenchus coffeae in yam tissues via RPA-CRISPR/Cas12a - Weichao Zhao; Mengli Lin; Yulong He; Jin Gao; Jiangli Zhang; Mingjun Li; Qingxiang Yang (Crop Protection, 2025)

Soil type-mediated root and leaf architectural modifications outweigh cadmium bioavailability in governing cadmium accumulation in rice - Gaoxiang HUANG; Jinbao ZHANG; Changfeng DING; Zhongyang XIONG; Jia LIU; Jingru HE; Haoyuan LÜ; Mingjun DING; Peng WANG; Yinghui JIANG; Lijun ZHOU; Zhenling LI (Pedosphere, 2025)

Leaf spot of yam caused by Schizophyllum commune in China - Ruifei Wang; Xuejia Wang; Liping Zhan; Xueyang Ren; Haibing Li; Yulong He; Hao Zhang; Yongkang Liu; Mingjun Li; Guixiao La; Qingxiang Yang (Australasian Plant Pathology, 2025)

Toltrazuril inhibits Toxoplasma gondii by potentially targeting pyrimidine metabolism - An Yan; Kai He; Mingjun Xiong; Xu Wang; Wanxiao Jin; Ruibin Wu; Bolin Xia; Weiwei Sun; Baoliang Pan (Pesticide Biochemistry and Physiology, 2025)

Selective enrichment of potential pathogens and antibiotic resistance genes derived from farmland residual microplastic films - Gaoxiang Huang; Hao Wang; Zhenling Li; Xiaokang He; Guangchun Shan; Peng Wang; Mingjun Ding; Chenghong Feng (Applied Soil Ecology, 2025)

Effect of mineral fertilizer addition on Pinus massoniana Lamb leaf litter decomposition and on amino acid concentration in a subtropical forest - Abdul Baess Keyhani; Wei He; Mingjun Teng; Zhaogui Yan; Monira Fayaz; Peng Zhao Hui; Wang Xiuyuan; Zemin Han; Abebe Assefa Gobena; Ataeei Abdul Rasool; Pengcheng Wang (Plant and Soil, 2025)

A rapid and visual detection method for Alternaria alternata, the causal agent of leaf spot disease on yam, based on RPA-CRISPR/Cas12a - Yulong He; Chenwei Tong; Huixuan Chen; Weichao Zhao; Liping Zhan; Ruifei Wang; Jiangli Zhang; Jin Gao; Chaochuang Li; Mingjun Li; Qingxiang Yang (Physiological and Molecular Plant Pathology, 2025)

A simple and effective algorithm to retrieve total suspended matter from GOCI data in Hangzhou Bay, China - Mingjun He; Shuangyan He; Shiming Lu; Yanzhen Gu; Feng Zhou; Xiaobo Ni; Chengyue Zhu; Peiliang Li (Science of The Total Environment, 2025)

Male mites are the promising targets for control of Dermanyssus gallinae (Acari: Dermanyssidae) based on the reproductive biology research - Boxing Liu; Jiaqi He; Qi Liu; Bohan Wang; Mingjun Xiong; Weiwei Sun; Baoliang Pan (Veterinary Parasitology, 2025)

Investigations of sodium droplet spreading and evaporation on surfaces with different wettability based on lattice Boltzmann simulations - Songsheng Tang; Kailun Guo; Ruibo Zhang; Mingjun Wang; Chenglong Wang; Xiaoqiang He; G.H. Su; Suizheng Qiu; Wenxi Tian (Annals of Nuclear Energy, 2024)

Deficient salience and default mode functional integration in high worry-proneness subject: a connectome-wide association study - Youxue Zhang; Mingjun Duan; Hui He (Brain Imaging and Behavior, 2024)

Synthesis, Structure and Luminescence Properties of Mn-doped MgAl2O4 Red-Emitting Phosphors with Varying Sintering Temperature - Jiahao Zha; Chongjun He; Fangzhou Chen; Hongwei Wang; Biao Dong; Lijuan Liu; Mingjun Xia; Chenguang Deng; Qian Li; Yuangang Lu; Huiting Chen (Journal of Fluorescence, 2024)

Loss of Gcn2 exacerbates gossypol induced oxidative stress, apoptosis and inflammation in zebrafish - Mingjun Tang; Weiyi Xia; Fei Song; Chengdong Liu; Xuan Wang; Huihui Zhou; Kangsen Mai; Gen He (Fish & Shellfish Immunology, 2024)

Depositional process and sediment dispersal pattern of mass transport complex on a slope with numerous elliptical depressions, northwestern South China Sea - Chao Liang; Chiyang Liu; Xinong Xie; Xiaohang Yu; Lei Huang; Jie Pan; Yunlong He; Hui Chen; Dongmei Tian; Honggang Mi; Mingjun Li; Hui Zhang (Sedimentary Geology, 2024)

Effect of mineral fertilizers on microorganisms community characteristic during leaf litter decomposition under Pinus massoniana in a subtropical forest - Abdul Baess Keyhani; Wei He; Mingjun Teng; Zhaogui Yan; Zhiyuan Ma; Jiaoyang Xu; Monira Fayaz; Changjian Zhou; Pujie Wei; Pengcheng Wang (Applied Soil Ecology, 2024)

Effect of various phosphorus levels on the extraction of Cd, the transformation of P, and phosphorus-related gene during the phytoremediation of Cd contaminated soil - Hongli Huang; Rule Zhao; Guanlin Guo; Yinhai He; Shuofu Chen; Yichun Zhu; Mingjun Xiao; Ping Liu; Junwu Liu; Yingchun Fang; Yaoyu Zhou (Environmental Research, 2024)

Two parallel methods for the three-dimensional CFD coupling simulation of shell and tube heat exchangers - Shiqi Wang; Shaopeng He; Mingjun Wang; Wenxi Tian; G.H. Su; Suizheng Qiu (Annals of Nuclear Energy, 2024)

Enhanced thermophilic dark fermentation of hydrogen production from food waste by Fe-modified biochar - Yongjun Yang; Jie Bu; Yong Wei Tiong; Shuai Xu; Jingxin Zhang; Yiliang He; Mingjun Zhu; Yen Wah Tong (Environmental Research, 2024)

Predicting vessel arrival times on inland waterways: A tree-based stacking approach - Jinyu Lei; Zhong Chu; Yong Wu; Xinglong Liu; Mingjun Luo; Wei He; Chenguang Liu (Ocean Engineering, 2024)

Genome dosage alteration caused by chromosome pyramiding and shuffling effects on karyotypic heterogeneity, reproductive diversity, and phenotypic variation in Zea–Tripsacum allopolyploids - Yingzheng Li; Xu Yan; Mingjun Cheng; Zizhou Wu; Qiyuan Zhang; Saifei Duan; Yong Zhou; Huaxiong Li; Shipeng Yang; Yulin Cheng; Wansong Li; Lulu Xu; et al. (Theoretical and Applied Genetics, 2024)

Evapotranspiration partitioning based on underlying conductance in a complex tree-grass orchard ecosystem in the humid area of southern China - Ningbo Cui; Shunsheng Zheng; Shouzheng Jiang; Mingjun Wang; Lu Zhao; Ziling He; Yu Feng; Yaosheng Wang; Daozhi Gong; Chunwei Liu; Rangjian Qiu (Agricultural and Forest Meteorology, 2024)

N-doped porous carbon-anchored zinc single-atom as an efficient and robust heterogeneous catalyst for glycerol carbonylation with urea - Jinghui Shi; Yunzuo Cui; Hao Sun; He Wang; Chunling Liu; Xiangxin Xue; Chuanbi Li; Longlong Geng; Jingyao Liu; Mingjun Jia (Chemical Engineering Journal, 2023)

Nuclear thermal coupling optimization of baffled NTP reactor - Zimian Duan; Jing Zhang; Zichao Han; Mingjun Wang; Yingwei Wu; Yanan He; Wenxi Tian; Siuzheng Qiu; G.H. Su (Annals of Nuclear Energy, 2023)

Optimized structural parameters and heat extraction capacity of a mixing device for constant pressure CO2 mineralization using alkaline waste - Wei Lu; Yang Yuan; Xiangming Hu; Guansheng Qi; Lulu Sun; Maoyuan Zhang; MingJun Wang; Min He (Environmental Science and Pollution Research, 2022)

Short-term exposure to six air pollutants and cause-specific cardiovascular mortality of nine counties or districts in Anhui Province, China - Guoao Li; Huanhuan Zhao; Mingjun Hu; Jialiu He; Wanjun Yang; Hanshuang Zhang; Zhenyu Zhu; Jinliang Zhu; Fen Huang (Environmental Science and Pollution Research, 2022)

Outdoor air pollution enhanced the association between indoor air pollution exposure and hypertension in rural areas of eastern China - Guoao Li; Huanhuan Lu; Wenlei Hu; Jianjun Liu; Mingjun Hu; Jialiu He; Fen Huang (Environmental Science and Pollution Research, 2022)

Ameliorating Inflammation in Insulin-resistant Rat Adipose Tissue with Abdominal Massage Regulates SIRT1/NF-κB Signaling - Tianjiao Gao; Shaotao Chen; Yiran Han; Dongmei Zhang; Yi Tan; Yutao He; Mingjun Liu (Cell Biochemistry and Biophysics, 2022)
It was the aim of this study to determine whether abdominal massage reverses high-fat diet-induced insulin resistance compared with RSV treatment. A total of sixty male Sprague-Dawley rats were randomly placed in one of four groups:the non-fat diet (NFD), the high-fat diet (HFD), the HFD with abdominal massage (HFD+ AM), and the HFD plus resveratrol (HFD+ RSV). For eight weeks, rats were fed high-fat diets to create insulin resistance, followed by six weeks of either AM or RSV. Molecular mechanisms of adipogenesis and cytokine production in rats with high-fat diets were investigated. The model rat adipose tissue showed significant improvements in obesity, glucose intolerance, and the accumulation of lipid in the body [the total cholesterol level (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C)], metabolic effects of glucose [The fasting blood glucose (FBG), Fasting insulin levels (FINS)], inflammatory status [interleukin-6 (IL-6) and tumor necrosis factor (TNF)-α, C-reactive protein (CRP)], and macrophage polarization after AM or RSV treatment. Further, AM increased SIRT1/NF-κB signaling in rat adipose tissue. Accordingly, in rat adipose tissue, our results indicate that AM regulates the secretion of proinflammatory cytokines, blood sugar levels, and related signaling pathways, contributing to improvement of IR, which may serves as a new therapeutic approach for the treatment for IR.

Effects of carbon dioxide and green space on sleep quality of the elderly in rural areas of Anhui Province, China - Guoao Li; Zhenyu Zhu; Mingjun Hu; Jialiu He; Wanjun Yang; Jinliang Zhu; Huanhuan Zhao; Hanshuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2022)

An atlas of CNV maps in cattle, goat and sheep - Yongzhen Huang; Yunjia Li; Xihong Wang; Jiantao Yu; Yudong Cai; Zhuqing Zheng; Ran Li; Shunjin Zhang; Ningbo Chen; Hojjat Asadollahpour Nanaei; Quratulain Hanif; Qiuming Chen; et al. (Science China Life Sciences, 2021)

Functional abnormalities of striatum are related to the season-specific effect on schizophrenia - Hui He; Huan Cao; Binxin Huang; Manxi He; Chi Ma; Dezhong Yao; Cheng Luo; Gang Yao; Mingjun Duan (Brain Imaging and Behavior, 2021)

A Hu sheep genome with the first ovine Y chromosome reveal introgression history after sheep domestication - Ran Li; Peng Yang; Ming Li; Wenwen Fang; Xiangpeng Yue; Hojjat Asadollahpour Nanaei; Shangquan Gan; Duo Du; Yudong Cai; Xuelei Dai; Qimeng Yang; Chunna Cao; et al. (Science China Life Sciences, 2021)

Altered asymmetries of diffusion and volumetry in basal ganglia of schizophrenia - Hui He; Cheng Luo; Ning Li; Zhiliang Li; Mingjun Duan; Gang Yao; Hongming Wang; Manxi He; Dezhong Yao (Brain Imaging and Behavior, 2021)

Arsenic exposure increased expression of HOTAIR and LincRNA-p21 in vivo and vitro - Jingwen Tan; Mingjun Sun; Quan Luo; Huiwen Sun; Mengjie Wang; Chenglan Jiang; Shuting Li; Yuefeng He (Environmental Science and Pollution Research, 2021)

Improved space–time sea surface salinity mapping in Western Pacific ocean using contingogram modeling - Mingjun He; Junyu He; George Christakos (Stochastic Environmental Research and Risk Assessment, 2020)

Understory vegetation removal reduces the incidence of non-additive mass loss during leaf litter decomposition in a subtropical Pinus massoniana plantation - Wei He; Xin Xu; Chenchen Zhang; Zhiyuan Ma; Jiaoyang Xu; Mingjun Ten; Zhaogui Yan; Ben Wang; Pengcheng Wang (Plant and Soil, 2020)

Estimates of linkage disequilibrium and effective population sizes in Chinese Merino (Xinjiang type) sheep by genome-wide SNPs - Shudong Liu; Sangang He; Lei Chen; Wenrong Li; Jiang Di; Mingjun Liu (Genes & Genomics, 2017)

Knockdown of endogenous myostatin promotes sheep myoblast proliferation - Chenxi Liu; Wenrong Li; Xuemei Zhang; Ning Zhang; Sangang He; Juncheng Huang; Yubin Ge; Mingjun Liu (In Vitro Cellular & Developmental Biology - Animal, 2014)

Extreme drought changes in Southwest China from 1960 to 2009 - Mingjun Zhang; Jinyun He; Baolong Wang; Shengjie Wang; Shanshan Li; Wenli Liu; Xuening Ma (Journal of Geographical Sciences, 2013)

Design and Evaluation of a Novel Evodiamine-Phospholipid Complex for Improved Oral Bioavailability - Qunyou Tan; Shan Liu; Xueliang Chen; Mingjun Wu; Hong Wang; Huafeng Yin; Dan He; Huarong Xiong; Jingqing Zhang (AAPS PharmSciTech, 2012)